Balanced scorecard for WAQF management and fundraising - Abdul Rahman, Azlan (2019)
Public university waqf management is akin to a non-profit charitable organisations in that its goal is typically to further its mission, which includes generating sufficient funds to continue to operate and serve the beneficiaries and stakeholders. Strategic management in public university waqf involves selecting the organisation's waqf goals, determining the strategic initiatives necessary to achieve specific objectives towards the goals, and establishing the methods necessary to ensure that the policies and activities are effectively implemented.Although the selection of most appropriate strategic management concepts is not so straightforward for the non-profit or charitable organisations, the use of these methods for charitable work in public university waqf and zakat is important to ensure its growth and sustainability. It is suggested that the public university waqf to be managed in a professional way of managing the assets within a modern administrative framework and in particular, the principles of stakeholders to be introduced in the waqf management. The Balanced Scorecard (BSC) is one of the useful strategic planning and management systems that organisations use to identify and improve various internal functions of their core business and their resulting external outcomes. It is used to measure and provide feedback to organisations. The BSC suggests that the organisation develops strategic objectives, measures (KPIs), targets, and initiatives (actions) relative to four perspectives, namely: stewardship, stakeholders, internal process and organizational capacity (or learning and growth). This paper shares an example of how the BSC approach can be adapted to the strategic management of public university waqf under the institutional advancement function.